The Association of Obesity with Walking Independent of Knee Pain: The Multicenter Osteoarthritis Study - Daniel K. White; Tuhina Neogi; Yuqing Zhang; David Felson; Michael LaValley; Jingbo Niu; Michael Nevitt; Cora E. Lewis; James Torner; K. Douglas Gross (Journal of Obesity)
Practice guidelines recommend addressing obesity for people with knee OA, however, the association of obesity with walking independent of pain is not known. We investigated this association within the Multicenter Osteoarthritis Study, a cohort of older adults who have or are at high risk of knee OA. Subjects wore a StepWatch to record steps taken over 7 days. We measured knee pain from a visual analogue scale and obesity by BMI. We examined the association of obesity with walking using linear regression adjusting for pain and covariates. Of 1788 subjects, the mean steps/day taken was 8872.9±3543.4. Subjects with a BMI ≥35 took 3355 fewer steps per day independent of knee pain compared with those with a BMI ≤25 (95% CI −3899, −2811). BMI accounted for 9.7% of the variability of walking while knee pain accounted for 2.9%. BMI was associated with walking independent of knee pain.